2022
DOI: 10.1177/10668969221095189
|View full text |Cite
|
Sign up to set email alerts
|

The Overexpression of Programmed Death-Ligand 2 in Uterine Adenosarcoma: Correlation with High-Grade Morphology, Mutant Type TP53 Expression and Clinical Outcomes

Abstract: Immunotherapy involving the programmed death-1 (PD-1)/the programmed death-ligand (PD-1/PD-L) blockade is an understudied tumor therapy approach in cases of adenosarcoma. PD-L1 and PD-L2, and tumor protein p53 (p53) were examined in 20 uterine adenosarcoma cases, and tumor-infiltrating lymphocytes and tumor-associated macrophages were counted in tumor tissue using immunohistochemistry. While CPS PD-L1 positivity with 1% and 10% cut-off values was observed in 40% and 10% of tumors, respectively, CPS PD-L2 posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…In endometrial sarcoma, PD-L2 expression was associated with mismatch repair (MMR)proficient tumors and lower OS rates when compared to PD-L1 expression [27]. Similar findings were reported in uterine adenosarcoma, which also showed that PD-L1 expression did not correlate with the density of TILs, but PD-L2 expression is positively correlated with TP53 mutation, which is associated with worse clinical outcomes [28].…”
Section: Immune Microenvironment and Biomarkers In Sarcomasupporting
confidence: 55%
“…In endometrial sarcoma, PD-L2 expression was associated with mismatch repair (MMR)proficient tumors and lower OS rates when compared to PD-L1 expression [27]. Similar findings were reported in uterine adenosarcoma, which also showed that PD-L1 expression did not correlate with the density of TILs, but PD-L2 expression is positively correlated with TP53 mutation, which is associated with worse clinical outcomes [28].…”
Section: Immune Microenvironment and Biomarkers In Sarcomasupporting
confidence: 55%